Pengaplikasian Platform Food Delivery Service Shopee Food dalam Memasarkan Produk Minuman Kamsia Boba Mataram - Phyta Rahima; Ria Rismayati (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The development of SME businesses in Indonesia is currently very much supported by their marketing capabilities. Marketing that is being carried out is now more upgraded than before, one of which is Digital Marketing starting from Endorse, Paid Promote and Social Media such as Instagram. However, for the last few years there have been several digital platforms that are specifically intended for culinary-based businesses (Food and Beverage), these digital platforms are quite positive for consumers as well as producers, in addition to saving time and energy, the costs incurred are not too large. One example of a digital platform that has a positive impact on users is Shopee Food. Shopee Food is a feature diversification of the shopee application other than shopeepay, shopeepaylater which is specifically made for food and beverage products. We as the Service Team are trying to help Kamsia boba Mataram, as one of the boba beverage businesses that has only been established for 2 years, to use the application to increase sales levels. The methods used in this service are 1) Identification of problems and solutions; 2) Process Design; 3) Implementation; 4) Validation and Evaluation; and 5) Conclusion. The stages of activities carried out by the community service team for Kamsia Boba Mataram SMEs were followed enthusiastically, this was proven by the use of the Shopee Food application as a means of promotion and sales by Kamsia Boba Mataram SMEs.